Marsolaire d’Amira de la Rosa. La violence occultée - Mercedes Ortega González-Rubio (Caravelle)
This article approaches gender-based violence in Caribbean Colombian literature, through the short story Marsolaire (1941), written by Amira de la Rosa. In the plot’s summary, an underage girl is raped by her godfather. No one, including the victim, seems to consider this as a violent act. Obscuring the abuse is a given problem depicted not only at intratextual level ; it also seems to have blinded the critics, making them accomplices of the offence, reproducing the masculine domination. Rape is a subject which has rarely triggered a profound meditation in the region’s literary manifestations, perhaps because it would imply a radical criticism of Caribbean society, therefore revealing the power relations which include part of an idiosyncrasy seen as legitimate and natural.